Factionalism in Political Parties: An Analytical Framework for Comparative Studies - Patrick Köllner; Matthias Basedau (German Institute of Global and Area Studies (GIGA), 2005)
Factionalism can affect the stability and institutionalization of parties and party systems and it can impact on the efficiency and legitimacy of political parties and political systems as a whole. Nevertheless, factionalism has only received scant attention in the comparative literature on political parties. As this paper shows, there is no dearth of conceptual approaches and hypotheses which can readily be used to advance the systematic analysis of factionalism. We survey the relevant literature and offer a comprehensive analytical framework to stimulate comparatively oriented and nuanced studies of the causes, characteristics and consequences of intra-party groups.
Keywords: 300; political parties; factionalism; party organization; electoral systems; party finance